Agricultural Machinery Adequacy for Handling the Mombaça Grass Biomass in Agroforestry Systems - de Morais, Gelton Fernando; Santos, Jenyffer da Silva Gomes; Han, Daniela [UNESP]; Ramos Filho, Luiz Octávio; Xavier, Marcelo Gomes Barroca; Schimidt, Leonardo; de Souza, Hugo Thiago [UNESP]; de Castro, Fernanda Ticianelli; de Souza-Esquerdo, Vanilde Ferreira; Albiero, Daniel (MDPI, 2023)
The current scenario of Agroforestry Systems (AFS) worldwide lacks specific machinery, resulting in practically all operations being carried out manually. This leads to a significant physical effort for small-scale farmers and limits the implementation of AFS to small areas. The objective of the study was to evaluate the suitability of existing machines for performing agroforestry tasks. This research utilizes Descriptive Statistics and Exponentially Weighted Moving Average methods to evaluate the data and compare the treatments, where different machines are used to cut Mombaça grass (Megathyrsus maximus Jacq): (i) costal brushcutter (CBC); (ii) tractor-mounted rotary brushcutter (RBC); and (iii) mini grain reaper machine (GRM). The experiments were conducted in Jaguariúna, São Paulo, Brazil. GRM is recommended for achieving greater biomass production, reducing raking time, and minimizing operational costs. CBC is suitable for smaller areas due to its affordability and slow operation, which requires significant physical effort. RBC is recommended for reducing working time, physical effort, and personnel costs, making it suitable for larger-scale contexts.
Keywords: agri-machines; agroforestry mechanization; forest farming; interrow production; machine suitability; Megathyrsus maximus Jacq